The role of flaxseed (Linum usitatissimum) in improving plasma lipid profiles: a literature review - Marcella, Marzha; Desak Made Wihandani; I Gusti Ayu Artini (Published by Universitas Gadjah Mada, 2025)
Several major risk factors contribute to cardiovascular diseases. One of these is dyslipidemia, an imbalance of plasma lipids such as total cholesterol (TC), low-density lipoprotein (LDL), triglycerides (TG), and high-density lipoprotein (HDL). While medications to lower lipids are widely used to improve lipid profiles, they have some limitations. Flaxseed is rich in ɑ-linolenic acid, phytosterols, and lignans, which can improve lipid profiles. This study aimed to review the potential effects of flaxseed on lipid metabolism. Data was gathered from research databases such as Google Scholar, PubMed, Science Direct, and Springer for the past 5 yr. About 1,527 scientific articles were found, but after eliminating duplicates and screening of title and abstract, only 45 full-text articles were assessed, with 16 selected. The result showed that ɑ-linolenic acid, phytosterols, lignans, and fibers in flaxseed improve TC, LDL, TG, and HDL through various mechanisms. In conclusion, flaxseed shows promise as a natural therapy for dyslipidemia, improving TC, LDL, VLDL, and TG levels, though HDL effects vary. Disparities are linked to demographics, form, dosage, and duration, highlighting the need for standardized research.